Avaliação do guaraná (Paullinia Cupana var. sorbilis) em pó como aditivo na dieta de suínos em terminação - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
The purpose of this study was evaluate the addition of Guarana (Paullinia cupana var. Sorbilis) in powder as an additive in finishing pig diets, through the diets digestibility, pigs growth performance and the economic viability on use of that product. In an 12-day digestibility experiment, total fecal collection method of 20 castrated male pigs of Topigs® commercial line with average weight of 61.8 ± 1.9 kg and 120 days-old, distributed in a randomized complete block design (DBC) with 4 inclusion levels (treatments) (0%, 1%, 2% and 4%) of guarana powder in diet and 5 repetitions (blocks) each. In the 30-day performance experiment, 48 commercial Topigs® pigs, with 24 males castrated and 24 females, both with initial average body weight 70.1 ± 7.9 kg and 120 days-old, distributed in a randomized complete block design (DBC) with 4 inclusion levels (treatments) (0% 1%, 2% and 3%) of guarana powder in the diets, with 6 replicates (block) and each repetition composed of 1 castrated male and 1 female. Carcass characteristics (PCQ, PCF, CC, EMT, EMT-P2, AOL and RG / C) were evaluated according to Brazilian Carcass Classification Method and economic analysis of the use of guarana powder as an additive. The performance data and the carcass characteristics were analyzed using the statistical package SAS LAB with verification of the adequacy of the data to the linear model, the analysis of variance was performed through PROC GLM of the SAS, after which the decomposition of the degrees of freedom of the factor level in its individual components (linear, quadratic) regression, through the orthogonal polynomials. A significant difference (P <0.05) was observed for most of the parameters, and there was a reduction in GDP and CDR and an increase in CA in relation to the control diet. For the WHR, RCF, CC, EMT, ET-PE2 and AOL it was observed that the addition of guarana powder had a negative quadratic effect in the results. In the economic analysis, it was verified the feasibility of the use of guarana powder as an additive, however, the performance results and carcass characteristics do not justify the adoption of levels used in the diet in this phase. Finally, the results of this research reinforce the action of guarana powder in metabolism of animals and humans with influence in reducing food consumption, inducing weight loss and reducing fat deposition.
Keywords: Suíno - Nutrição; Guaraná - Suplemento; Guaraná - Desempenho; Carcaça de animais; Suinocultura - Brasil; CIÊNCIAS AGRÁRIAS: ZOOTECNIA: NUTRIÇÃO E ALIMENTAÇÃO ANIMAL